Firm Growth through Diversification into Contract Electronic Manufacturing sector: Pressac Communication - Mhavarkar, Bhavana (2012)
Electronic Industry is highly competitive, volatile and high-tech industry. Electronic firm’s performance is depended on day-today’s market. In such an intense competitive world survival is the biggest challenge for Electronic firms. Firms who have stagnant business cannot hold their position in marketplace for long time; they will have to grow their business. Pressac Communication one of the Electronic Manufacturing Companies seeks to grow their business through diversification. Pressac tends to enter into Contract Electronic Manufacturing sector. But the main issue is Pressac is not sure if entering into Contract Electronic Manufacturing is worth for their business. Pressac has already gone through a huge loss before through bad acquisition. It is very essential for Pressac to study market behaviour of Contract Electronic manufacturing sector; which will help them to make strategic decision for their business. At the same time Pressac has to identify their internal capabilities which will help to determine if Pressac has enough capabilities to enter into the new business. In short, this report helps to identify the possibilities of Pressac Communication to enter into the Contract Electronic Manufacturing sector by studying the market environment of Contract Electronic Manufacturing sector and internal capabilities of Pressac Communication.